PROCEDURE FOR THE FORMATION OF A LAND PLOT FOR A HOUSING COOPERATIVE AND ITS REGISTRATION IN THE STATE LAND CADASTRE - Shpik , Н. (Bulletin of Lviv National Environmental University. Series «Architecture and Construction», 2025)
The regulatory and legal framework for the process of forming land plots within settlements has been reviewed. According to Article 38 of the Land Code of Ukraine, residential and public development lands include plots used for residential development, public buildings and structures, and other communal facilities. This category of land must be used in accordance with the general plan of the settlement, other urban planning documentation, and the land management plan, while also complying with building regulations. The definition of a housing cooperative (HC) and the adjacent territory (AT), along with the conditions for their establishment, is outlined in accordance with the Land Code of Ukraine. The step-by-step process for creating an association of co-owners of a multi-apartment building is described in detail, with a particular emphasis on the mandatory registration of the HC as a legal entity. Establishing land ownership rights for housing cooperatives is crucial, as it ensures that third parties cannot use the land plot, allows for better control over land use, and protects against unauthorized constructions, land leasing, and illegal parking. The procedure for preparing the necessary documents for obtaining permission for housing cooperatives to allocate land plots is described. An example is given using the housing cooperative “Chumatska 14” in Lviv, detailing the process of registering this plot in the State Land Cadastre database and the procedure for submitting land management documentation for approval. The long-standing practice of registering land plots adjacent to apartment buildings for housing cooperatives has been analyzed, revealing that there are currently no reliable guarantees or mechanisms in place to prevent corruption within the land sector. Thus, the only way to ensure the security of the territory surrounding a building is to remove it from the control of officials, although this approach does not provide complete certainty or reliability.